Circuit of life - Mohtarrudin, Norhafizah; Abdul Wahit, Mohamad Aizat; Ahmad, Siti Anom; Baharuddin, Mohd Nasir (Universiti Putra Malaysia Press, 2017)
The brain is the most complex organ in the human body. It exerts centralised control over the other organs by rapid and coordinated responses through the neuronal circuit. The brain circuit travels up and down the neuroaxis, from right to left brain and vice versa, back and forth from all parts of the brain at different levels within the thalamus, hypothalamus, forebrain, midbrain, medulla, cerebellum, and spinal cord.